Motivación Hacia Las Clases De Educación Física En Preadolescentes Mexicanos De Acuerdo Al Género - García, Perla Jannet Jurado; Valenzuela, Concepción Soto; Chávez, Juan Francisco Aguirre; Longoria, Raúl Josué Nájera; Fernández, Fernando Mondaca (European Scientific Journal, ESJ, 2018)
The aim of the present research was to compare the motivation towards physical education profiles from Mexican elementary school students. The total sample included 274 students (140 girls) from Chihuahua City, Mexico; children’s ages ranged from 10 to 12 years. A quantitative approach with a descriptive transversal design was used. Results from a one-way MANOVA followed by univariate analyses of variance showed that compared to boys, girls report higher levels of intrinsic motivation (F = 19.188, p <.001), integrated regulation (F = 13.730, p <.001), identified regulation (F = 11.902, p <.001) and introjected regulation (F = 6.937, p <.01); no significant differences were encountered in external regulation and demotivation. These results indicate that, in general, women show a better profile of motivation towards physical education classes than men. However, it is necessary to develop more research because the issue transcends the scope of the present study.